ANALYSIS OF REACTION RATES ON COMBUSTION OF CNG - AIR WITH DILUENT ARGON - Gunawan, Iwan (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2019)
Natural gas was formed millions of years ago through the process of decomposition of plants and animals. This natural gas is composed mostly by methane and a number of other gases in small quantities such as ethane, propane, butane. We know that the heating value of oil and gas such as CNG is very different, where the heating value of CNG (Compressed Natural Gas) is higher than oil (premium). This will have an impact that if an accident occurs due to human error or a fault the tool will cause an explosion, so it is important to know the flammability limit of CNG mixtures with air. In this study a mixture of hydrogen gas fuel and oxygen gas oxidizer was used as fuel in the driver for initial initiation, while CNG fuel was used with driven air oxidizer. The fuel mixture was tested on a circle section horizontal flammability test pipe with a total length of 6000 mm (1000 mm in the driver section and 5000 mm in the driven section), a 50 mm diameter inside the room temperature and a pressure of 100 kPa driver. At driven the pressure is still 100 kPa and the CNG concentration changes with variations of 0 kPa to 40 kPa CNG with air and a total pressure mixture of 100 kPa. From the results of the study it was found that the flammability limit of CNG between 5 kPa at the lower flammability limit and 15 kPa at the upper flammability limit, detonation did not occur on the width of the flammability limit. In the range between 1-4 kPa and 16-40 kPa CNG there is no combustion reaction, and in the range 5-15 deflagration occurs.